Education of nanotechnologies in Mexico and the social implications, risks and the environment - Villa Vázquez, Laura Liliana (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
Currently, no economic sector worldwide does not incorporate nanotechnologies (NTs) in its production processes or in a wide variety of products distributed in global markets. Several countries, including Mexico, do not have programs that compile information regarding the development of these technologies. This paper systematizes information regarding higher education institutions (HEIs) that grant undergraduate or postgraduate academic degrees in NTs in Mexico. In addition, it explores whether the curricula include the issues of social implications, risks, and the environment. Mexico is the second country in Latin America, after Brasil, to endorse nanotechnology development.